2015
DOI: 10.1111/acps.12423
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the association. Toxoplasma gondii in schizophrenia, bipolar disorder, and addiction: systematic review and meta‐analysis

Abstract: These findings suggest that T. gondii infection is associated with several psychiatric disorders and that in schizophrenia reactivation of latent T. gondii infection may occur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
313
6
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 382 publications
(379 citation statements)
references
References 134 publications
(241 reference statements)
21
313
6
4
Order By: Relevance
“…They showed that toxoplasmosis likely strongly increases the risk of schizophrenia, bipolar disorder, obsessive-compulsive disorder, as well as epilepsy and migraines. For reviews (see Flegr, 2015;Sutterland et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…They showed that toxoplasmosis likely strongly increases the risk of schizophrenia, bipolar disorder, obsessive-compulsive disorder, as well as epilepsy and migraines. For reviews (see Flegr, 2015;Sutterland et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…There were two studies that looked at obsessive compulsive disorder, one with a sample size of 42 patients and the other with a sample size of 12 patients (OR = 3.4, 95% CI: 1.73 -6.6.8, p < 0.001). Although the findings for OCD are significant, they should be interpreted with caution since they are small sample sizes and did not clearly separate the OCD diagnosis from Generalized Anxiety Disorder [33].…”
Section: Relationship Between Toxoplasma Gondii and Psychosismentioning
confidence: 64%
“…Le « premier temps » prendrait place durant la grossesse. De nombreux événements survenant pendant cette période comme des infections virales par le cytomégalovirus (CMV), par exemple, ou par des parasites (comme Toxoplasma gondii) ont été associés au déve-loppement ultérieur de ces maladies psychiatriques, en particulier dans les troubles bipolaires et la schizophrénie [42,43]. Ces mêmes pathogènes ont également le potentiel de réactiver in vitro des éléments de la famille HERV-W [44].…”
Section: La Séquence D'activation Des Herv Dans Les Troubles Psychotiunclassified